PENGARUH SOCIAL MEDIA MARKETING TWITTER TERHADAP TERBENTUKNYA BRAND IMAGE RESTORAN BURGER GABOH PEKANBARU - Rizal, Veby Zilfania; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The existence of the internet and information communication technologieâsitâs makes the use of new media in marketing communications. The emergence ofsocial media marketing can be used as well as for the interaction to consumers,called social media marketing. One of social media marketing is now popularamong businesses including restaurants, namely Twitter. Through 140 characters,tweets of any business can market their business at the same place / make upbrand, to be known and remembered in the minds of consumers, and designing thebrand communication strategy that is viewed positively by consumers whichraises brand image. The purpose of this research is to determine how much theinfluence of social media marketing Twitter towards the brand image formation ofBurger Gaboh Restaurant at Pekanbaru.The theory used in this study is S-O-R theory by Hovland and cybercommunity theory by Severin and Tankard. The method used in this study is aquantitative method of explanation. Researchers collected data usingquestionnaires and documentation. The location of this study, in Burger GabohRestaurants, located at Suka Terus street 30 Pekanbaru. The number of samplesfor this study as many 259 respondents, using techniques accidental sampling. Inorder to know how much the influence these two variables, researchers used asimple linear regression analysis. As for processing test data questionnaire,carried out using the program of Statistics Product anf Service Solution (SPSS)Windows version 20.The result of this study indicate that the alternative hypothesis is accepted.Which means there is a strong the influence of social media marketing Twittertowards the brand image formation of Burger Gaboh Restaurant at Pekanbaru .This result is the regression coefficient values obtained in this study is Y = 0,542+ 0,856 X with significant level of Î± 0,05. The coefficient of determinations (r2) of0,714 which means that 71,4% of the influence of social media marketing Twittertowards the brand image formation of Burger Gaboh Restaurant at Pekanbaru.While the remaining 28,6% is influenced by other variables outsides of this study.Keywords : Social Media, Marketing, Brand Image